Paths to Resilience and Success: The Role of Male Support in the Professional Growth of Female Teachers in Afghanistan - Sadiyah Ehsan Fjellrik; Marte Blikstad-Balas (Journal of Asian Social Science Research, 2025)
Education remains a powerful force for societal transformation and Afghanistan provides a complex context in which to examine its impact—particularly through the experiences of female teachers. This study explores the narratives of twelve Afghan women educators from urban and suburban areas in a western province, focusing on the year following the Taliban’s return to power in 2021. Employing a critical narrative inquiry approach, the research sheds light on the often-overlooked role of male family members in supporting women’s educational and professional lives. Grounded in Freire’s critical pedagogy, hooks’s theories of becoming and self-actualization, and Bourdieu’s concept of social capital, the study identifies four key themes: (1) the role of male support in the professional development of female teachers; (2) advocacy beyond the classroom; (3) deep cultural and religious grounding; and (4) resistance and resilience. Central to the study is the nuanced concept of male support, which participants defined as engaging in meaningful dialogue, affirming women’s choices, encouraging their societal contributions, or simply listening openly. Participants—ranging in age from their mid-20s to late 60s—described how male relatives challenged social expectations to protect and promote their educational and professional goals. While these men often acted as allies, the study also critically examines how such support may inadvertently reinforce patriarchal norms. These findings contribute to the growing body of scholarship on education in conflict zones and offer important implications for gender-sensitive education policy, teacher training, and advocacy efforts in Afghanistan and similar contexts.